Révéler ce qui fait patrimoine pour penser le renouvellement urbain des cités d’habitations à bon marché de Grenoble - Ryma Hadbi (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This research project consists of questioning what makes heritage in three of Grenoble’s low-rent housing neighborhoods built between 1920-1930: La Capuche, L’Abbaye and Jean Macé. Although originally similar in terms of their construction context, they experienced different architectural, urban and social transformations over time. What makes heritage can be approached as a living, constantly evolving process, integrating mutations, changes and ruptures and articulating three patrimonial values: historical value, use value and renewal value. For that, the focus of this article is on individual and collective memories, uses and life stories of the people who have lived in these housing estates for decades. What counts in this approach is the value granted to the inhabitants and their attachments. This work equally demonstrates the importance of thinking about what makes heritage through attachment to place, in order to think about the urban renewal of these estates which are full of emotional significations. In this sense, urban memory is a way to simultaneously read the past, the present and the possible future of a site by postulating that the memory somehow holds the "genes" of the place. It can thus serve as the heritage itself, the common good from which the renewal of these memorial and emotionally rich places can be made.